Volatile organic compounds emitted by Trichoderma species mediate plant growth. Issue 1 (December 2016) - Lee, Samantha; Yap, Melanie; Behringer, Gregory; Hung, Richard; Bennett, Joan
Abstract Background ManyTrichoderma species are applied as biofungicides and biofertilizers to agricultural soils to enhance crop growth. These filamentous fungi have the ability to reduce plant diseases and promote plant growth and productivity through overlapping modes of action including induced systemic resistance, antibiosis, enhanced nutrient efficiency, and myco-parasitism.Trichoderma species are prolific producers of many small metabolites with antifungal, antibacterial, and anticancer properties. Volatile metabolites ofTrichoderma also have the ability to induce resistance to plant pathogens leading to improved plant health. In this study, Arabidopsis plants were exposed to mixtures of volatile organic compounds (VOCs) emitted by growing cultures ofTrichoderma from 20 strains, representing 11 differentTrichoderma species. Results We identified nineTrichoderma strains that produced plant growth promoting VOCs. Exposure to mixtures of VOCs emitted by these strains increased plant biomass (37.1–41.6 %) and chlorophyll content (82.5–89.3 %).Trichoderma volatile-mediated changes in plant growth were strain- and species-specific. VOCs emitted byT .pseudokoningii (CBS 130756) were associated with the greatestArabidopsis growth promotion. One strain, T. atroviride (CBS 01-209), in our screen decreased growth (50.5 %) and chlorophyll production (13.1 %). Similarly, tomatoes exposed to VOCs fromT. viride (BBA 70239) showed a significant increase in plant biomass (>99 %), larger plant size, and significant development of lateral roots. We also observed that the tomato plant growths were dependent on the duration of the volatile exposure. A GC–MS analysis of VOCs fromTrichoderma strains identified more than 141 unique compounds including several unknown sesquiterpenes, diterpenes, and tetraterpenes. Conclusions Plants grown in the presence of fungal VOCs emitted by different species and strains ofTrichoderma exhibited a range of effects. This study demonstrates that the blend of volatiles produced by actively growing fungi and volatile exposure time in plant development both influence the outcome of volatile-mediated interactions. Only some of our growth promoting strains produced microbial VOCs known to enhance plant growth. Compounds such as 6-pentyl-2H -pyran-2-one were not common to all promoting strains. We found that biostimulatory strains tended to have a larger number of complex terpenes which may explain the variation in growth induced by differentTrichoderma strains.